Countering Islamic Radicalism among Indonesian University Students: An Investigation on Social Media Using LINE Official Account - Nasih, Ahmad Munjin; Darwis,; Hamid, Abdulloh (Journal of Al-Tamaddun, 2023)
Social media platforms continue to be vastly utilized in university contexts as channels for the dissemination of zealous religious ideas. As a group, students are vulnerable to radicalism and are easily affected by extremist perceptions. This study investigated how the LINE Official account could be utilized to spread moderate Islamic perspectives in the Muslim student community in Indonesia’s universities. It also examined how such an account could contribute to the mitigation of radicalism among students. This study contributes significantly to the literature because most extant research on counterradicalism movements remains centered on actions involving numerous stakeholders. It is hence necessary to initiate individual-focused movements that employ technology. The data used for the present study were obtained by analyzing conversations and comments available on the LINE platform. The study’s findings suggest that LINE Official accounts can be employed as tools to oppose radicalism and spread moderate views among university students in Indonesia.